The moderating role of anxiety sensitivity in the co-occurrence of anxiety and depression symptoms among clinically anxious children. Issue 3 (2nd August 2018) - Viana, Andres G.; Woodward, Emma C.; Hanna, Abigail E.; Raines, Elizabeth M.; Alfano, Candice A.; Zvolensky, Michael J.
The co-occurrence between anxiety and depression symptoms among children with anxiety disorders is well-known, yet there is considerable heterogeneity in terms of explanatory factors. Although cognitive–affective processes have been hypothesized to play a prominent role, surprisingly, no research to date has examined the role of anxiety sensitivity in this co-occurrence. The present investigation examined the role of anxiety sensitivity in the co-occurrence of anxiety and depression symptoms among clinically anxious children. We expected that anxiety sensitivity would moderate the co-occurrence between anxiety and depression symptoms, such that higher anxiety would be related to higher depression among boys and girls with high (but not low) anxiety sensitivity. Participants ( N = 44, age range = 8–12 years; 52% female; 52% African American) were interviewed with the Anxiety Disorders Interview Schedule-IV: Children and Parent Versions and completed self-report measures of anxiety sensitivity, anxiety, and depression symptom severity. Controlling for child age, moderation analyses revealed that higher anxiety was related to higher depression only among girls with high anxiety sensitivity. Among girls with low anxiety sensitivity, the relation between anxiety and depression symptoms was not significant. Anxiety and depression symptoms were strongly correlated among clinically anxious boys irrespective of their levels of anxiety sensitivity. Anxiety sensitivity is an important factor related to anxiety–depression symptom co-occurrence among clinically anxious females in particular. Targeted interventions focused on anxiety sensitivity reduction may prove useful for reducing anxiety–depression symptom co-occurrence among clinically anxious girls. Future research should explore additional moderators that may explain the high correlation between anxiety and depressive symptoms observed among clinically anxious boys.